2020
DOI: 10.3390/ijerph17155525
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Feelings of Loneliness and Attitudes towards Physical Education in Contemporary Adolescents According to Sex, and Physical Activity Engagement

Abstract: Background: Currently, adolescents grow up consuming a large amount of multimedia content and lead a sedentary lifestyle. As a result, emerging trends show greater feelings of loneliness. The present research seeks to describe adolescents’ attitudes towards Physical Education (PE), indices of loneliness and physical activity (PA) engagement. Further, it analyses associations between attitudes towards PE as a function of PA engagement and considers sex, loneliness and school year repetition as factors. Method: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 75 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…The literature has shown that some psychosocial outcomes of adolescents can be in uenced by obesogenic behaviors such as PA, diet, and SB [2,11,13]. In addition, there is evidence that adolescents with healthier obesogenic behavior pro les have better socialization, with lower chances of loneliness [5,9,10]. Our ndings also highlight the fact that many adolescents have lifestyles de ned by the coexistence of favorable and unfavorable health behaviors [14].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The literature has shown that some psychosocial outcomes of adolescents can be in uenced by obesogenic behaviors such as PA, diet, and SB [2,11,13]. In addition, there is evidence that adolescents with healthier obesogenic behavior pro les have better socialization, with lower chances of loneliness [5,9,10]. Our ndings also highlight the fact that many adolescents have lifestyles de ned by the coexistence of favorable and unfavorable health behaviors [14].…”
Section: Discussionmentioning
confidence: 55%
“…The problem that arises is that: (a) being in an obesogenic cluster can make socialization di cult, increasing social isolation [9,10]; and (b) clusters that combine positive and negative behaviors can still favor better socialization and psychological disposition in adolescents when compared to clusters that mostly combine risk behaviors [2,11].…”
Section: Introductionmentioning
confidence: 99%
“…The literature has shown that some psychosocial outcomes of adolescents can be influenced by obesogenic behaviors such as PA, diet, and SB [ 2 , 11 , 15 ]. In addition, there is evidence that adolescents with healthier obesogenic behavior profiles have better socialization, with lower chances of loneliness [ 5 , 9 , 10 ]. Our findings also highlight the fact that many adolescents have lifestyles defined by the coexistence of favorable and unfavorable health behaviors [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The problem that arises is that: (a) being in an obesogenic cluster can make socialization difficult, increasing social isolation [ 9 , 10 ]; and (b) clusters that combine positive and negative behaviors can still favor better socialization and psychological disposition in adolescents when compared to clusters that mostly combine risk behaviors [ 2 , 11 ]. The pioneering study by Iannotti and Wang (2013) [ 11 ], which investigated clusters of obesogenic behaviors and their impact on physical and mental health in adolescents in the United States, found that the group with the highest sedentary behavior and the highest proportion of non-healthy diet, but who still moderately met physical activity criteria or consumed fruits and vegetables daily, had lower levels of body dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…The second group of psychological problems is based on the unsatisfied need for love (Padial-Ruz et al, 2020). It is not necessarily that the parent does not love the child enough.…”
Section: Literature Reviewmentioning
confidence: 99%